Presentations for the 2023 PNG Rural Household Survey: Report Launch - Schmidt, Emily; Hayoge, Glen; Koima, Joe; Dom, Michael (International Food Policy Research Institute, 2024)
From May to December 2023, the International Food Policy Research Institute (IFPRI) implemented a rural household survey that collected detailed data on rural household food consumption and expenditures, agricultural production practices, employment profiles, child and mother 24-hour diet recall, and child anthropometry measurements across 14 provinces in Papua New Guinea (PNG). This survey represents the most comprehensive effort to collect detailed consumption and expenditure data since the 2009/10 PNG Household Income Expenditure Survey, completed in 2010.